A mixed methods analysis of the magnitude and associated factors of time management practice among primary hospital employees in North Gondar, Ethiopia - Muluken Genetu Chanie; Amsalu Feleke; Solomon Mekonnen; Mamo Dereje Alemu; Gojjam Eshetie Ewunetie (Public Library of Science (PLoS), 2021)
Time management contributes to work efficiency, maintaining balance, and job satisfaction by promoting productivity and success. Most people believe they have so much to do and not enough time, and they attribute their unmet expectations, poor results, and low productivity to a lack of time. The aim of this study was to determine the magnitude and associated factors of time management practice among primary hospital employees in North Gondar, Ethiopia.From March 15 to April 28, 2017, a hospital-based cross-sectional mixed methods (both quantitative and qualitative) study design was conducted in North Gondar Zone. For the quantitative part, pre-tested, standardized questionnaires; as well as an interviewer guide for the qualitative part of the study were used for data collection. Using a random sampling technique, 391 employees were completed the questionnaires. A multivariate and bi-variate logistic regression analysis at AOR with a 95% CI and a p-value of < 0.5 were used to identify significant factors of the study. For qualitative data, thematic content analysis was performed. A total of 391 participants (a response rate of 92.6%) took part in the study. The number of participants who practice time management was 56.4% (95% CI: 49.3%, 61.7%). Organizational policies (AOR: 2.16; 95% CI: 1.02, 4.68), performance appraisal systems (AOR: 2.11; 95% CI: 1.32, 4.66), compensation and benefits system (AOR: 4.18; 95% CI: 2.18, 7.99), employee planning experience (AOR: 2.86; 95% CI: 1.42, 5.75), and residence (AOR: 2.08; 95% CI: 1.08, 4.01) were found predictors of time management practice among primary hospital employees. Overall, there was a moderate level of time management practice in the study area. Significant factors found were organizational policies, compensation and benefits packages, performance appraisal systems, planning experience, and residency. Therefore, managers need to develop an intervention to address all the above factors in order to improve time management practice of primary hospital employees at work.